Knowledge Transfer in Global Software Development - Leveraging Ontologies, Tools and Assessments - Salger, Frank; Sauer, Stefan; Engels, Gregor; Baumann, Andrea (5th IEEE International Conference on Global Software Engineering (ICGSE 2010))
To be successful with global software development (GSD), development knowledge needs to be shared among the developers and stakeholders, and the quality of the exchanged information must be assured. Therefore, mature processes, methods and tools have to be in place. If a unified and integrated solution does not exist, this impedes the exchange of knowledge (and the migration of people between projects). In GSD, such a diversity can lead to new problems: offshore development teams have to repeatedly re-adjust to method variants used by the respective business units. This can lead to misinterpretation of information and risks for project success. We report on re-aligning the varying software engineering methods and unifying the methodology throughout Capgemini sd&m. We also standardized quality assurance procedures and tightly integrated them with the engineering methodology. By this, we arrived at a comprehensive company-wide Enterprise Software Engineering Model that effectively supports knowledge transfer from clients to the onshore and offshore team.

MDDAUI 2010 Workshop Report - Van den Bergh, Jan; Meixner, Gerrit; Sauer, Stefan (Proc. 5th Intl. Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI 2010))

Pattern-based Generation of Test Plans for Open Distributed Processing Systems - Güldali, Baris; Sauer, Stefan; Winkelhane, Peter; Jahnich, Michael; Funke, Holger (Proceedings of 5th International Workshop on Automation of Software Test (AST 2010), ICSE Workshop)

Architecture-Driven Derivation of Performance Metrics - Brüseke, Frank; Sancar, Yavuz; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '10), Paderborn, Germany)

Effort Comparison of Model-based Testing Scenarios - Güldali, Baris; Mlynarski, Michael; Sancar, Yavuz (Proceedings of 3th International Conference on Software Testing, Verification, and Validation Workshops)

Test Case Generation for Visual Contracts Using AI Planning - Schnelte, Matthias; Güldali, Baris (INFORMATIK 2010, Beiträge der 40. Jahrestagung der Gesellschaft für Informatik e.V. (GI))

Ultrasonically-assisted Hydrothermal Method for Ferroelectric Material Synthesis - Ageba, Ryo; Kadota, Yoichi; Maeda, Takafumi; Takiguchi, Norihito; Morita, Takeshi; Ishikawa, Mutsuo; Bornmann, Peter; Hemsel, Tobias (Journal of Korean Physical Society)
The hydrothermal method enables the production of high-quality piezoelectric materials. In this study, we propose to irradiate the reaction solutions with ultrasonic power during the hydrothermal method to obtain a shorter reaction time and a smooth film surface. A high-pressure reaction container for the ultrasonic transducer was newly developed, and the ultrasonically-assisted hydrothermal method was examined by using this container. The effect of ultrasonic assist on the synthesis of lead-zirconate-titanate (PZT) thin films and (K,Na)NbO$_{3}$ powders was verified. Thicker PZT film, thickness around 10 ${μ}$m, could be obtained in one process, and (K,Na)NbO$_{3}$ powder was synthesized in half the previous reaction time.
Keywords: Hydrothermal method; High-power ultrasonic; PZT thin film; Lead-free piezoelectric materials

Ultrasonic Transducer for the Hydrothermal Method - Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Ageba, Ryo; Kadota, Yoishi; Morita, Takeshi (Journal of Korean Physical Society)
Direct ultrasound irradiation is advantageous to increase the efficiency of the hydrothermal method which can be used for the production of piezoelectric thin films and lead free piezoelectric ceramics. To apply ultrasound directly to the process transducer prototypes were developed regarding the boundary conditions of the hydrothermal method. LiNbO$_{3}$ and PIC 181 were proven as feasible materials for high temperature resistant transducers ($≥ 200^° C$). Resistance of the transducers horn against the corrosive mineralizer was achieved by using Hastelloy C-22. The efficiency of the ultrasound assisted hydrothermal method depends on the generated sound field. Impedance and sound field measurements have shown that the sound field depends on the filling level and the position and design of the transducer.
Keywords: High-temperature transducer; Hydrothermal method; Lithium-niobate transducer

Modeling of Piezoelectric Langevin Transducers by Using Mixed Transfer Matrix Methods - Fu, Bo; Li, Chao; Zhang, Jianming; Huang, Zhenwei; Hemsel, Tobias (Journal of Korean Physical Society)
In the modeling of piezoelectric Langevin transducers using usual transfer matrix methods, some simplifications have been adopted. This leads to reduction of the model quality. A mixed transfer matrix method is employed in the modeling of Langevin transducers, where the pre-stressed bolt is modeled as a separate four-pole element, which is connected to other elements in parallel. Based on the mixed transfer matrix method, the four (six)-pole element description of the piezoelectric Langevin transducer is built up and the total transfer matrix relation is derived. The resonance frequencies of the transducer are calculated and then measured using the impedance analyzer (HP4192). Experimental result shows that the mixed transfer matrix method has better modeling quality than the usual transfer matrix method for the vibration analysis of piezoelectric Langevin transducers.
Keywords: Piezoelectric langevin transducer; Transfer matrix method; Four (six)-pole element description; Pre-stressed bolt

Reibungsdämpfung in ausgedehnten, verschraubten Fügestellen - Hölzl, Johannes Sebastian; Sextro, Walter (PAMM)
Bei der Konstruktion von Maschinen ist es oftmals erforderlich, Schwingungen minimal zu halten. Um z.B. die Lebensdauer zu erhöhen, Material einzusparen oder den Geräuschpegel gering zu halten muss oft ein großer Aufwand zur Dämpfung von auftretenden Schwingungen betrieben werden. In vielen technischen Anwendungen werden Einzelteile miteinander verschraubt. Diese Fügestellen können gezielt und mit wenig Aufwand zur Schwingungsdämpfung herangezogen werden. Die Berechnung des dynamischen Verhaltens verschraubter Strukturen stellt immer noch eine Herausforderung dar. Es wurde eine Methode entwickelt, um den eingeschwungenen Zustand elastischer, miteinander verschraubter Körper mit rauen Fügestellen bei periodischer Anregung zu berechnen. Als Basis dienen Finite Elemente Modelle der einzelnen Teile, deren Freiheitsgrade durch modale Kondensation reduziert werden. Unter Anwendung des Verfahrens von Ritz und Galerkin wird eine Näherungslösung für den eingeschwungenen Zustand des nichtlinearen, gekoppelten Systems ermittelt. Abhängig von den Schraubenvorspannkräften sowie den bestimmenden Parametern der Kontaktflächen, Rautiefe und Reibungskoeffizient, kann die Systemantwort berechnet und optimiert werden. Um die Berechnungsmethode zu verifizieren wurden Experimente durchgeführt. Der Vergleich zwischen Messung und Rechnung zeigt eine gute Übereinstimmung. ({©} 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)